Greener Synthesis, Characterization, and Antimicrobiological Effects of Helba Silver Nanoparticle-PMMA Nanocomposite - Manal A. Awad; Awatif A. Hendi; Khalid M. O. Ortashi; Amnah B. Alanazi; Batool A. ALZahrani; Dina A. Soliman (International Journal of Polymer Science)
Nanocomposites are characterized as a multiphase material where one of the phases has a dimension in the nanoscale. There has been huge enthusiasm for the commercialization of nanocomposites for an assortment of uses including medicinal, electronic, and basic. The general motivation behind this study was on the development of silver nanoparticles, due to the present enthusiasm encompassing these metals due to their exceptional properties which are not quite the same as the relating bulk material. A novel, simple, cost-effective, nontoxic, and environmentally friendly technique was developed for synthesizing silver nanoparticle- (AgNP-) poly(methyl methacrylate) (PMMA) nanocomposite using Trigonella foenum-graecum (Helba) aqueous extract. UV-visible spectroscopic analysis was carried out to assess the formulation of AgNPs. The particle size distribution of AgNPs was determined by dynamic light scattering (DLS). The average size of green AgNPs was about 83 nm. Images of spherical green nanoparticles were characterized using transmission electron microscopy (TEM). The resultant green AgNPs were added slowly to polymer (PMMA) solution. The AgNPs encapsulated within the polymer chains were characterized by X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR). Modification of thermal stabilities of AgNP/PMMA nanocomposites was confirmed using thermogravimetric analysis (TGA). The green AgNP/PMMA nanocomposites showed improved thermal stabilities. The green AgNP/PMMA nanocomposite film proved antimicrobial in water microbiological testing. Thus, the key findings of the work include the use of a safe and simple nanocomposite, which had marked antibacterial activity and potential application in water filtration.